Analysis of serum phase proteins and emulsifiers on the whipping capabilities of aerated emulsions: From the perspective of air-liquid interface rheology - Xie, Pengkai; Lai, Junqi; Xie, Rui; Zou, Shuo; Lee, Yee Ying; Tan, Chin Ping; Wang, Yong; Zhang, Zhen (Elsevier B.V., 2025)
In aerated emulsions, the serum phase plays a crucial role in determining whipping capabilities. However, the effects of serum phase components on emulsion properties remain largely unexplored and continue to be a mystery. This study takes a micro-level approach, focusing on the air-liquid interfacial rheology by incorporating different types of surfactants (proteins and emulsifiers) into the serum phase. It systematically explores the effects on the serum phase interface, emulsion properties, whipping capabilities, and foam stability in a stepwise manner. Proteins only slightly affect the strength of the air-liquid interface, primarily improving the capacity to trap bubbles at the initial whipping stage, thereby boosting the overrun of the aerated emulsion. The high viscoelastic modulus of the interface membrane is greatly influenced by the presence of solid lipid nanoparticles of glycerol monostearate (GMS SLN), leading to a reduction in whipping time and improved surface-mediated partial coalescence. This ultimately enhances the quality and stability of the foam system. Tween 80, due to its hydrophilic properties, is able to quickly adsorb at the air-liquid interface using the Gibbs-Marangoni mechanism. This helps to expedite the end of the whipping process and ultimately improves the foam quality. On the contrary, glycerol monooleate (GMO), a lipophilic emulsifier for liquids, struggles to effectively adsorb at the interface, leading to decreased stability of the air-liquid interface in the system and resulting in poor whipping capabilities. This paper delves into the mechanism by which different surfactants affect the whipping capabilities of aerated emulsions through an analysis of serum phase composition, laying the groundwork for enhancing formulation design.